2016
DOI: 10.1142/s0192415x16500439
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin Prevents Hypoxic Pulmonary Hypertension via Anti-Oxidant Effects in Rats

Abstract: Punicalagin (PG), a major bioactive ingredient in pomegranate juice, has been proven to have anti-oxidative stress properties and to exert protective effects on acute lung injuries induced by lipopolysaccharides. This study aimed to investigate the effects of PG treatment on hypoxic pulmonary hypertension (HPH) and the underlying mechanisms responsible for the effects. Rats were exposed to 10% oxygen for 2 wk (8 h/day) to induce the HPH model. PG (5, 15, 45[Formula: see text]mg/kg) was orally administered 10[F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…These violent actions lead to stasis of blood flow and disruption of gastric microvessel in the other hand, although pre-treatment with PCG significantly elevated mucosal level of NO, it failed to change level of PGE2, indicating involvement of NO and passive role of PGE2 in the mechanism of PCG's gastroprotective effects. PCG improved NO-cGMP signaling [33] as well it quenched of the superoxide anion which consumes NO for the generation of the cytotoxic peroxynitrite [34]. Furthermore, NO enhanced maintenance of mucosal blood flow [35] resulting in improving in gastric mucosal defense as shown in the current study.…”
mentioning
confidence: 57%
“…These violent actions lead to stasis of blood flow and disruption of gastric microvessel in the other hand, although pre-treatment with PCG significantly elevated mucosal level of NO, it failed to change level of PGE2, indicating involvement of NO and passive role of PGE2 in the mechanism of PCG's gastroprotective effects. PCG improved NO-cGMP signaling [33] as well it quenched of the superoxide anion which consumes NO for the generation of the cytotoxic peroxynitrite [34]. Furthermore, NO enhanced maintenance of mucosal blood flow [35] resulting in improving in gastric mucosal defense as shown in the current study.…”
mentioning
confidence: 57%
“…Punicalagin is a phytochemical isolated from pomegranate juice and has many pharmacological activities due to its high antioxidant content (Xu et al, 2015); also it has been reported that punicalagin used for treatment of lung diseases in animal models (Peng et al, 2015). Shao et al (2016) during an investigation on hypoxia induced PH in rats shows that treatment with punicalagin improves hemodynamic indicators and induce relaxation by enhancing NO-cGMP signaling pathway in PAs. Also this phytochemical reduces oxidative stress and raises mRNA expression of MMP-9, HIF-1a, VEGFA, NF-kB and TNF-a in lung tissue of animals.…”
Section: Punicalaginmentioning
confidence: 99%
“…Chinese herb Naofeikang and Ruscogenin have additional therapeutic potential against PH by down regulating the inflammatory reaction and macro phase infiltration (Bi et al, ; Han et al, ). Radix Astragali (Fabaceae) (Chen, Ruan, Xi, Si, & Zhang, ), Allium sativum (Amaryllidaceae) (Sun & Ku, ), Luteolin (Lamiaceae) (Occhiuto & Limardi, ), Rhoifolin (Rutaceae) (Occhiuto & Limardi, ), and Punicalagin (Punica granatum) (Shao et al, ) have reported for producing the measurable reduction in mean arterial blood pressure, pulmonary vascular remodeling and collagen deposition, which are significantly liable to the pathogenesis of PH. Erigeron breviscapus (Asteraceae) has potent antiproliferative action on smooth muscle cells (Zheng, Xie, Gao, & Zhang, ).…”
Section: Pharmacological Interventions and Their Molecular Aspectsmentioning
confidence: 99%
“…Whereas, Tetrandrine upregulate the expression of protein kinase 1, superoxide dismutase, glutathione in MCT-induced PH in rats (Wang et al, 2016). Moreover, Levosimendan, (Calcium sensitizer and new dual acting non-arrhythmogenic drug) was reported to revert right ventricular failure in PH (Hansen et al, 2017).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
See 1 more Smart Citation